Global interference during early visual processing: ERP evidence from a rapid global/local selective task - Beaucousin, Virginie; Simon, Grégory; Cassotti, Mathieu; Pineau, Arlette; Houdé, Olivier; Poirel, Nicolas (Frontiers in Psychology, 2013)
Visual perception depends on the integration of local elements of a visual scene into a global frame. Evidence from behavioral studies shows that (1) the detection of the global frame is faster than the detection of the local parts, a phenomenon called the global advantage, and that (2) an interference of the global shape is also present during local processing. Together, these effects are called the global precedence effect. Even if the global advantage appears to impact neural processing as early as the first 100 msec post-stimulus, previous studies failed to find a global interference effect before 200 msec post-stimulus. Using for the first time a rapid display of letter component stimuli during a global/local selective task in which conditions with perceptual conflict, congruent and incongruent conditions were considered, the present event-related potential study shows a global interference effect occurring as early as the time range of the N1 component. In particular, only congruent stimuli elicited similar N1 amplitude during the global and local tasks, whereas an increased of the N1 amplitude during the global task was observed (as compared to the local task) for both stimuli with perceptual conflict and incongruent stimuli. This finding corroborates the recent neural models of human visual perception.